Clinical Performance Validation of 4 Point-of-Care Cervical Cancer Screening Tests in HIV-Infected Women in Zambia. Issue 3 (July 2016) - Chibwesha, Carla J.; Frett, Brigitte; Katundu, Katundu; Bateman, Allen C.; Shibemba, Aaron; Kapambwe, Sharon; Mwanahamuntu, Mulindi H.; Banda, Susan; Hamusimbi, Chalwa; Polepole, Pascal; Parham, Groesbeck P.
Abstract : Objectives: We sought to determine the clinical performance of visual inspection with acetic acid (VIA), digital cervicography (DC), Xpert human papillomavirus (HPV), and OncoE6 for cervical cancer screening in an HIV-infected population. Materials and Methods: HIV-infected women 18 years or older were included in this cross-sectional validation study conducted in Lusaka, Zambia. The screening tests were compared against a histological gold standard. We calculated sensitivity, specificity, positive and negative predictive values, positive and negative likelihood ratios, and odds ratios using cervical intraepithelial neoplasia grade 2 or worse (CIN 2+) and grade 3 or worse (CIN 3+) thresholds. Results: Between January and June 2015, a total of 200 women were enrolled. Fifteen percent were screen positive by VIA, 20% by DC, 47% by Xpert HPV, and 6% by OncoE6. Using a CIN 2+ threshold, the sensitivity and specificity of VIA were 48% (95% CI = 30%–67%) and 92% (95% CI = 86%–95%), respectively. Similarly, the sensitivity and specificity of DC were 59% (95% CI = 41%–76%) and 88% (95% CI = 82%–93%), respectively. The sensitivity and specificity of Xpert HPV were 88% (95% CI = 71%–97%) and 60% (95% CI = 52%–68%), respectively. Finally, the sensitivity and specificity of OncoE6 were 31% (95% CI = 16%–50%) and 99% (95% CI = 97%–100%), respectively. Conclusions: VIA and DC displayed moderate sensitivity and high specificity. Xpert HPV performed equivalently to currently approved HPV DNA tests, with high sensitivity and moderate specificity. OncoE6 displayed excellent specificity but low sensitivity. These results confirm an important role for VIA, DC, and Xpert HPV in screen-and-treat cervical cancer prevention in low- and middle-income countries, such as Zambia. Abstract : Visual inspection with acetic acid, digital cervicography, and Xpert human papillomavirus should be considered in future screen-and-treat cervical cancer prevention programs, including for HIV-infected women.